G232 Use of Infliximab in Children with Refractory Kawasaki Disease. (4th June 2013) - Singh, S; Suri, D; Manojkumar, R; Narula, N; Gupta, A; Rawat, A
Abstract : Introduction: The aetiology of Kawasaki diasese (KD) is still an enigma. It is known that cytokines have a major role to play in the pathogenesis of this condition. There is evidence of TNF-α activation during the acute phase of KD. Although the drug of choice for treatment of KD is still intravenous immunoglobulin (IVIg), approximately 10–15% patients may not respond to the first dose of IVIg. In such cases, an additional dose of IVIg can be given. Infliximab, a TNF-α inhibitor, is also being increasingly used in such situations. We present our experience with use of infliximab in 9 patients with refractory KD at a tertiary care cente. Patients and methods: We diagnosed 112 children with KD during the period January 2007 – November 2012. The diagnosis of KD was based on the American Heart Association criteria. All children underwent detailed echocardiography examinations by a paediatric cardiologist. Standard treatment protocols (IVIg 2 g/kg along with aspirin) were used in the management of these children. In addition, 9 children with KD received infliximab (REMICADE) during this period. The drug was used in doses of 5–7 mg/kg and given intravenously, . Indicationas for using infliximab were as follows: refractory KD in 6 children; 3 children had come in late (>3 weeks) and had coronary artery abnormalities (CAA) at presentation. 7 patients had developed CAA abnormalities before infliximab therapy: transient mild dilatation-2; aneurysms-3; giant aneurysms-2. Results: Complete response to therapy with cessation of fever occurred in 7/9 patients. Platelet count and C-reactive protein concentrations decreased following infliximab infusion in all, except 2. The latter 2 patients, on follow-up, progressed and developed features consistent with systemic onset juvenile idiopathic arthritis. 4 children with mild CAA (dilatation/small aneurysms) showed complete resolution on follow-up; 2 children with giant aneurysms showed no further progression. No side-effects were noted and there were no significant infusion reactions. Conclusion: Infliximab may have a role in refractory KD, especially when there are CAA. In older children, the use of infliximab is also more economical than IVIg.This has therapeutic implications in resource constrained settings of a developoing country.